2017
DOI: 10.1038/nmat5053
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum non-toxic antiviral nanoparticles with a virucidal inhibition mechanism

Abstract: Viral infections kill millions yearly. Available antiviral drugs are virus-specific and active against a limited panel of human pathogens. There are broad-spectrum substances that prevent the first step of virus-cell interaction by mimicking heparan sulfate proteoglycans (HSPG), the highly conserved target of viral attachment ligands (VALs). The reversible binding mechanism prevents their use as a drug, because, upon dilution, the inhibition is lost. Known VALs are made of closely packed repeating units, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
374
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 360 publications
(415 citation statements)
references
References 41 publications
8
374
1
Order By: Relevance
“…In addition to cancer treatments, AuNPbased/assisted therapy can be applied to cardiovascular diseases, intestinal microora and infection. [144][145][146] Bacterial infection especially caused by antibiotic-resistant bacteria is becoming a more serious threat to the human health. Small molecule-modied AuNPs showing excellent antibacterial activity can serve as attractive alternatives to conventional antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cancer treatments, AuNPbased/assisted therapy can be applied to cardiovascular diseases, intestinal microora and infection. [144][145][146] Bacterial infection especially caused by antibiotic-resistant bacteria is becoming a more serious threat to the human health. Small molecule-modied AuNPs showing excellent antibacterial activity can serve as attractive alternatives to conventional antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Low cytotoxicity is one of the most important requirements for any potential antiviral agent; Fatima et al described the non-toxicity (CC 50 > 500 µg/mL) of synthesized green nanoparticles and their precursors tested in the same way by the MTT assay on Vero cells [20]. Cagno et al also reported the lack of significant toxicity at similar concentrations (CC 50 ≥ 100-300 µg/mL) of gold NPs coated with undecanesulfonic acid (MUS)-containing ligands and their pre-MUS ligand [21].…”
Section: Discussionmentioning
confidence: 99%
“…11-mercaptoundecane sulfonate sodium salt (MUS) was synthesized according to a previously reported protocol. [20] All solvents were ACS grade and used without further purification.…”
Section: Materials For Ampnp Synthesismentioning
confidence: 99%